Ginsenoside Rg1 modulates medial prefrontal cortical firing and suppresses the hippocampo-medial prefrontal cortical long-term potentiation - Ghaeminia, M. (Elsevier B.V., 2021)
10.1016/j.jgr.2017.03.010